2002
DOI: 10.2134/jeq2002.3000
|View full text |Cite
|
Sign up to set email alerts
|

Runoff and Drainage Losses of Atrazine, Metribuzin, and Metolachlor in Three Water Management Systems

Abstract: Rainfall can transport herbicides from agricultural land to surface waters, where they become an environmental concern. Tile drainage can benefit crop production by removing excess soil water but tile drainage may also aggravate herbicide and nutrient movement into surface waters. Water management of tile drains after planting may reduce tile drainage and thereby reduce herbicide losses to surface water. To test this hypothesis we calculated the loss of three herbicides from a field with three water management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 28 publications
(41 reference statements)
2
10
0
Order By: Relevance
“…The drain flow reduction of 6 to 54% found in this study is in agreement with the findings of 8 to 64% reductions in other field studies conducted on silt and clay loam (Tan et al, 1999;Gaynor et al, 2002;Drury et al, 2009;Fang et al, 2012;Sunohara et al, 2014;Williams et al, 2015). The effect of CD was clearly strongest at the highest regulation level (70 cm), which agrees with earlier studies (Evans et al, 1995;Wesström and Messing, 2007).…”
Section: Impact Of Controlled Drainage On Hydrologysupporting
confidence: 93%
“…The drain flow reduction of 6 to 54% found in this study is in agreement with the findings of 8 to 64% reductions in other field studies conducted on silt and clay loam (Tan et al, 1999;Gaynor et al, 2002;Drury et al, 2009;Fang et al, 2012;Sunohara et al, 2014;Williams et al, 2015). The effect of CD was clearly strongest at the highest regulation level (70 cm), which agrees with earlier studies (Evans et al, 1995;Wesström and Messing, 2007).…”
Section: Impact Of Controlled Drainage On Hydrologysupporting
confidence: 93%
“…James et al [26] (http:// www.hortnet.co.nz/publications/nzpps/proceedings/old/ 94nzpps.htm) measured 0.88 mg/kg of atrazine in soil following application at the same rate as that used to simulate our low exposure (1.5 kg/ha); this is an order of magnitude lower than for soil measured in our high-dose group (8.1 mg/kg) but similar to that for our low-dose group (0.64 mg/kg). Similarly, an application rate of 1.1 kg/ha yielded peak soil concentrations of 0.97 mg/kg of atrazine [27]. Thus, our low exposure resulted in soil concentrations similar to those found in soil following actual spray applications.…”
Section: Discussionsupporting
confidence: 57%
“…Notwithstanding these benefits, controlled tile drainage is currently not a practice that is ubiquitous in tile-drained regions throughout the world, and little is known about how this practice, when imposed en masse at a watershed scale, impacts the sources and degree of fecal pollution in surface water. A majority of experimental research on CTD is set at the field/plot scale and has focused primarily on other pollution targets (18)(19)(20). However, recently Schmidt et al (21) found that CTD could potentially increase instantaneous loads and concentrations of fecal indicator bacteria and Campylobacter spp.…”
mentioning
confidence: 99%